Analisis Motivasi Terhadap Peningkatan Kinerja Karyawan Pada PT Angkasa Pura Supports Bandara Internasional Sultan Hasanuddin - Muhtazib Muhtazib; Mattarima Mattarima; Evitasari Evitasari (CEMERLANG : Jurnal Manajemen dan Ekonomi Bisnis, 2021)
The aim of the research is to determine the relationship between motivation and employee performance and to find out how to increase employee work motivation. This research method uses quantitative research methods. The data used in this research are primary and secondary data and questionnaires were administered as research samples. The results of this research show that Motivation (X1) has a positive and significant effect with a value of 0.000 with a significance level of 0.05.